Corporate governance : case study of Kelon. - Kuan, Xiao Hua. (2008)
This study examines the corporate governance system in China, with Guangdong Kelon Electrical Holdings Company (“Kelon”) as our basis for discussion. Kelon, a once-renowned refrigerator maker, is now in dire straits due to a series of commercial misdeeds.